Experimental evaluation of bonded overlay and NSM GFRP bar strengthening on flexural behavior of precast prestressed hollow core slabs. (1st August 2016) - Kankeri, Pradeep; Prakash, S. Suriya
Highlights: Seven full scale hollow core slabs are strengthened and tested under flexure. Effect of bonded overlay, NSM strengthening and their hybrid combination is studied. Only bonded overlay increased the strength by 89% without reducing the ductility. Only NSM strengthening increased the strength by 100% with reduced ductility. Hybrid strengthening increased the ultimate strength by about 200%. Abstract: A hollow core slab is a precast prestressed concrete member with longitudinal cores that reduce its self-weight. Strengthening of prestressed hollow core slabs is required for several reasons to maintain their structural integrity. The main focus of this research is to understand the flexural behavior of hollow core slabs and failure modes with hybrid strengthening techniques including bonded overlay and near surface mounted (NSM) glass fiber reinforced polymer (GFRP) bars. The test variables include different strengthening techniques such as (i) bonded overlay with and without shear keys, (ii) NSM GFRP rebar and (iii) hybrid strengthening combination which includes a thin bonded overlay in the compression region and NSM GFRP bars in the tension region. A total of seven full scale slabs were cast, strengthened and tested until failure. Test results show that bonded overlay increases the flexural strength by 89% without much compromise on the ductility when compared to control slab, whereas NSM GFRP bar strengthening increases the strength by about 100% but with reduced ductility. Hybrid strengthening led to a highest increase in the ultimate strength (about 200%) and ductility when compared to only NSM and only bonded overlay strengthening.